Core competencies for academic librarians: a framework model from systematic literature review. - Awan, Waqar Ahmad; Soroya, Muhammad Shahid; Azhar, Sana (Performance Measurement & Metrics, 2026)
Purpose: This research paper aims to develop a comprehensive framework model for sustainable competency development among university-level academic librarians in Asia. Design/methodology/approach: Recognizing 21st-century competencies as distinct from those of the 20th, relevant literature was searched between 2000 and 2025 across two databases: Scopus and Library and Information Science & Technology Abstracts. Additionally, a scholarly web search engine (Google Scholar) was also searched so that maximum document retrieval could be ensured. Subsequently, duplicate articles were excluded. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) design was followed to write this paper. Findings: The synthesis of the literature revealed a four-element framework model comprising elements of written policies, stakeholders, competencies and methods for improvement. It is found that information technology, management, information literacy, soft skills, professional skills and trustworthiness are essential competencies for information professionals. The model also suggests that these skills can be enhanced through self-learning, one-on-one training, internship modules and training sessions. The stakeholders that may organize training sessions comprise library and information science (LIS) schools, continuous education program designers and professional LIS bodies. Research limitations/implications: The proposed framework provides a valuable guide for LIS schools, organizations designing continuing education programs, and professional LIS bodies. This framework may help them improve the competencies of LIS students and practitioners through identified methods in the identified competencies directions. Originality/value: This is the first study to investigate the competencies of Asian information professionals through a systematic literature review and synthesis of previously published research articles from 48 countries and three disputed territories across the continent of Asia.